Scope of Algae as Third Generation Biofuels - Behera, Shuvashish; Singh, Richa; Arora, Richa; Sharma, Nilesh Kumar; Shukla, Madhulika; Kumar, Sachin (Frontiers in Bioengineering and Biotechnology, 2015)
An initiative has been taken to develop different solid, liquid and gaseous biofuels as the alternative energy resources. The current research and technology based on the third generation biofuels derived from algal biomass have been considered as the best alternative bioresource that avoids the disadvantages of first and second generation biofuels. Algal biomass have been investigated for the implementation of economic conversion processes producing different biofuels such as biodiesel, bioethanol, biogas, biohydrogen and other valuable co-products. In the present review, the recent findings and advance developments in algal biomass for improved biofuel production. This review discusses about the importance of the algal cell contents, various strategies for product formation through various conversion technologies, and its future scope as an energy security.